Epstein-Barr virus-associated T/natural killer-cell lymphoproliferative disorder in children and young adults has similar molecular signature to extranodal nasal natural killer/T-cell lymphoma but shows distinctive stem cell-like phenotype - Ng, Siok-Bian (TAYLOR & FRANCIS LTD, 2021)
10.3109/10428194.2014.983099